2013
DOI: 10.1016/j.bpj.2012.11.2129
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis of Force Generation by the Mitotic Motor Kinesin-5

Abstract: Double-stranded DNA viruses, including tailed bacteriophages and mammalian herpesviruses, package their genomes into pre-formed protein capsids. The packaging process is driven by a molecular complex known as the packaging motor. This motor is a ring-shaped oligomeric ATPase that utilizes the chemical energy from ATP binding and hydrolysis to perform the mechanical work. We have recently presented a detailed mechanochemical characterization for the bacteriophage phi29 motor, a homo-pentamer that translocates D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 0 publications
7
22
0
Order By: Relevance
“…However, immediately above and protruding away from the nucleotide binding site, density corresponding to the Cut7MDspecific loop5 is clearly visible ( Figure 1B, C). As was previously seen at lower resolution (Britto et al, 2016), this Cut7MD loop5 conformation is distinct from that observed for AMPPNP-bound human kinesin-5 loop5 (Goulet et al, 2012;Parke et al, 2010). The sequences of Cut7 and human kinesin-5 in this region of the motor domain are distinct ( Figure S2), and conformational sensitivity of this loop to even small changes in other kinesin-5s has been observed ( Figure 1C; (Behnke-Parks et al, 2011;Bell et al, 2017;Bodey et al, 2009;Liu et al, 2011).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…However, immediately above and protruding away from the nucleotide binding site, density corresponding to the Cut7MDspecific loop5 is clearly visible ( Figure 1B, C). As was previously seen at lower resolution (Britto et al, 2016), this Cut7MD loop5 conformation is distinct from that observed for AMPPNP-bound human kinesin-5 loop5 (Goulet et al, 2012;Parke et al, 2010). The sequences of Cut7 and human kinesin-5 in this region of the motor domain are distinct ( Figure S2), and conformational sensitivity of this loop to even small changes in other kinesin-5s has been observed ( Figure 1C; (Behnke-Parks et al, 2011;Bell et al, 2017;Bodey et al, 2009;Liu et al, 2011).…”
Section: Resultssupporting
confidence: 72%
“…Distal to the nucleotide binding site, the Cut7MD N-and C-termini coincide to form the functionally important cover neck bundle (CNB; Figure 1D) (Goulet et al, 2012;Khalil et al, 2008). Density corresponding to the C-terminal neck linker, which connects the Cut7 motor domain to the rest of the protein, is clearly visible docking along the length of the motor domain and directed towards the MT plus end.…”
Section: Resultsmentioning
confidence: 99%
“…This "stapling" conformation implies a model in which the two heads cross-bridge consecutive tubulin dimers and thereby promote protofilament stability. Surprisingly, isolated Eg5 head domains, which bind to a single tubulin (Goulet et al, 2012), also promote microtubule polymerization, which rules out lattice crossbridging as the primary Eg5 polymerase mechanism. Hence, we considered a model in which Eg5 promotes microtubule polymerization by modulating the curvature of tubulin.…”
Section: A New Role For Eg5 In Mitotic Spindle Morphogenesismentioning
confidence: 99%
“…While kinesin-family motor domains are relatively conserved, there are still significant differences in the motors kinetic cycles and also their necks and neck-linkers (7)(8)(9)(10)(11)(12)(13)(14), and we are only starting to understand the extent to which molecular variations adapt the motors to their specific functions (see e.g. [15][16][17][18].…”
mentioning
confidence: 99%